Drivers for COVID 19 vaccine hesitancy among breastfeeding women in Eastern tribal state, India - Kiran Trivedi; Shikha Anand; Prami Atta; Manisha Kujur; Anit Kujur; Shashibala Singh; Anupa Prasad; Kumari Asha Kiran (Journal of Family Medicine and Primary Care)
Background: In the COVID-19 pandemic age, vaccination hesitancy also known as vaccine refusal is a cause for worry since it hinges on the five Cs of confidence, complacency, convenience, calculation, and shared responsibility. The current study was to pinpoint the elements that contribute to breastfeeding women's hesitation to receive the coronavirus disease-19 (COVID-19) vaccine. Materials and Methods: A cross-sectional observational study was carried out at the Department of Obstetrics and Gynaecology, Tertiary Care Hospital, Ranchi, Jharkhand. Result: Out of 365 nursing mothers, 242 (66.3%) were hesitant to get the COVID-19 vaccination. Those who chose not to receive the COVID-19 vaccination mostly belong to those aged 18 to 25 (38.1%), living in rural regions (44.9%), and belonging to non-tribal ethnic groups (41.1%). On application of logistic regression, it was found that rural areas had 3 times higher rate of vaccine hesitancy than urban residents, and that husbands' education levels up to the 12th grade had a 3.55 times higher rate and 5 times agriculture by husband's occupation, which was statistically significant (P value less than 0.05) The most prevalent grounds for rejection were fear of side effects (85.8%) and worry of adverse effects on newborns (83.48%). Conclusion: Both husband and wife, who had completed high school and were aware of the vaccination, were fearful of the COVID-19 vaccine. Concerns about the side effects and undesirable effects of vaccination on their newborns were the main reasons for refusal.